KANDUNGAN BAHANG KERING, SERAT KASAR DAN AIR DAUN ECENG GONDOK YANG DIFERMENTASI DENGAN BERBAGAI LEVEL EM4 PADA LAMA WAKTU YANG BERBEDA - Muhammad Nur Hidayat; Khaerani Kiramang, Surati (State Islamic University (UIN) Alauddin, 2015)
ABSTRACT. This study was conducted in the Basic Laboratory of Animal Science, Faculty of Science and Technology of the State Islamic University of Makassar, and the Laboratory of Food Chemistry, Faculty of Animal Husbandry, Hasanuddin University, Makassar. This study aimed to determine the effect of EM-4 levels and the influence of long fermentation time (Crude Fiber, Dried Materials and Water) Eichhornia crassipes. The method is based on research conducted in (completely randomized design factorial) with 3x3 factorial with four replications, treatment composition as follows: The first factor ; EM- 4 level P0 (0 % EM-4), P1 (1 % EM4), and P2 (1.5 % EM4) and the second factor: the time of T0 fermentation (7 days), T1 (14 days), and T2 (21 days). Based on the results of various analysis and discussion, it can be concluded that the level of provision of 1.5 % EM-4 influences on crude fiber content of dry materials and water, while long fermentation time significantly affects on the water content and lower fiber content .